Cortical frequency-specific plasticity is independently induced by intracortical circuitry. (6th March 2018) - Kong, Lingzhi; Wang, Shaohui; Liu, Xiuping; Li, Liang; Zeeman, Michael; Yan, Jun
Highlights: Cortical plasticity was induced by intracortical electrical stimulation. Such plasticity is frequency-specific tuning shift. The frequency-specific tuning shift does not lie on the auditory thalamus. Abstract: Auditory learning induces frequency-specific plasticity in the auditory cortex. Both the auditory cortex and thalamus are involved in the cortical plasticity; however, the precise role of the intracortical circuity remains unclear until the contributions of the thalamocortical inputs are controlled. Here, we induced cortical plasticity by local activation of the primary auditory cortex (AI) via intracortical electrical stimulation (ES) in C57 mice and found a similar pattern of cortical plasticity was induced by ESAI when the auditory thalamus was inactivated or remained active during the ESAI . The best frequencies (BFs) of the recorded cortical neurons shifted towards the BFs of the electrically stimulated ones. In addition, the BF shifts were linearly correlated to the BF differences between the recorded and stimulated cortical neurons. More importantly, the ratio of the linear function with thalamic inactivation was nearly the same as the ratio of the linear function in the control condition. Our data show that cortical frequency-specific plasticity was induced by ESAI with or without the thalamic inactivation; thus intracortical circuitry can be independently responsible for cortical frequency-specific plasticity.